8x+16=6x-18

Simple and best practice solution for 8x+16=6x-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x+16=6x-18 equation:


Simplifying
8x + 16 = 6x + -18
Reorder the terms:
16 + 8x = 6x + -18
Reorder the terms:
16 + 8x = -18 + 6x
Solving
16 + 8x = -18 + 6x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-6x' to each side of the equation.
16 + 8x + -6x = -18 + 6x + -6x
Combine like terms: 8x + -6x = 2x
16 + 2x = -18 + 6x + -6x
Combine like terms: 6x + -6x = 0
16 + 2x = -18 + 0
16 + 2x = -18
Add '-16' to each side of the equation.
16 + -16 + 2x = -18 + -16
Combine like terms: 16 + -16 = 0
0 + 2x = -18 + -16
2x = -18 + -16
Combine like terms: -18 + -16 = -34
2x = -34
Divide each side by '2'.
x = -17
Simplifying
x = -17

You can always share this solution

See similar equations:

| 4x+10=7x+13 | | -2(t-2)+4t=6t-8 | | 8m=210 | | 2*x-4=23 | | -4(3x-5)=3-(8x+7) | | 6x+2x=-48 | | 6+10y=4y | | x-7(5x)=113 | | 3x+3-1=3x+2 | | 2(x-2)+5x= | | 2(x+4)+4=4x-2(-4+x) | | 16+36X-2X-2X+12=4(23) | | 9*3+-6+7= | | 16-2n=10 | | 6f+11=-2f-13 | | 3b+4.4=6.2-6b | | 12p=2p+5 | | 3b-12=21b | | 3x+2(3x-1)+8=24 | | 9n-n+17=-19+4n | | x-(5-3x)=7x+13a | | -x-5x+5=-4x+11 | | 12x+23=2(3x+8)+6x+7 | | 4(m-1)-6=8-3(m+2) | | 4=0.666x+9+0.333x | | 4(x+5)=12+2x | | x^2+2x=9-6x | | 20+4j=3j | | 15+3(x+2)=-7+2(x+1) | | 1.43=.4y-.6y | | 8b(y-5)=6y-18 | | .50x+.30(180-x)=.40(180) | | 6x+5x-8=47 | | 2(a+4)=4a-(2a+4) | | 5a+4(3a-8)=c+13a | | h=61.412+46.2 | | 3b+39=10b | | 9k^2+5=1 | | 0.333(x+6)=1 | | 5t-9=-3t-7 | | 5n-15-8n=-10 | | 5t-9=-3t-9 | | 8t-10=3t | | 8g-6=2(5-g) | | 6-5(3x-3)=4x+7 | | 6x+18=10x | | x(x-2)-2=2(x-5)+4x | | 0.666x+11=7 | | 4x+6=12x-9 | | -10x+10=0 | | 2(x+15)=-8 | | 8x-6=2(5-g) | | -8m+2=-7m+8 | | 5x-(6-x)=4(1-x) | | 7x^2-62x=0 | | y^2-11y-16=0 | | 23-r=18 | | -10=-5x-(25) | | 6(5c-8)-20=11(2k-3)+3k | | y^2-13y-16=0 | | -3=h+4 | | 3xy=x+8 | | 27=-5x-8 | | 8(x+2)+4x=16 | | 2x^2-62=0 |


Related pages


derivative of lnx xsquare root of 96 simplifiedgraph x 3ygraph y 2x-6log10 x 1greatest factor calculatorprime factorization of 94210-22x 2-25 factoredfg x calculatorroman numerals cix63-15whats the prime factorization of 144356.92x 6y 813337xan2 bn cfactor 3x 2 17x 10lcm of 4 and 3prime factorization of 212xx 4x3.14159265derivative 3 xx6300757-100write each percent as a decimal calculatorfind the prime factorization of 165prime factorization of 900250 000 euros to dollarsmath step by step problem solverwhat is the prime factorization of 174200-1541947 in roman numeralsy sin3xprime factorization of 132solve 2x 3y 9100-68graph y sin 3xsolve 4y 1 2y 8800-8883-424w solutionstan 2x sec 2x3c & 5ssimplify 4x 6xhow to solve cos 2xy 9ypercent solversolve fg xderivative of 5lnx200-165calculator to divide fractions1800-1300roman numerals for 199020 qt galsin 2x cos 2xsin 2x cos xwhat is the square root of 441what is the prime factorization of 232derivative cos 3xlcm finderderivative of ln 9xwhat is the prime factorization for 443cos 2xsimplify 2x 2xhow to add fractions with a calculatorcommon multiples of 6 and 8how to enter a fraction on a calculatorlcm of 144prime factorization of 504graph x 2y 5solution equation calculator3000 dollars in rupees